Docentes de música na educação básica: um estudo sobre identidades profissionais - Wille, Regiana Blank (2013)
This research had the objective of investigating how the professional identity of a music educator is built in the public schools in Pelotas/RS. The results found in this research contribute to clarify the various dimensions of the professional performance of a music educator in elementary schools in the southern region of the state, taking into account life experiences lived in a social and cultural context that constantly changes. A qualitative approach was used in this research as well as semi-structured interviews to collect the data analyzed. The empirical field was the public schools run by the city of Pelotas and ten active music teachers and music educator took part in this study. The theoretical basis for the analysis were Dubar s (2005) view about professional identities, Nóvoa (1995, 1999) and Marcelo (2009) and some others that consider identities as something dynamic and complex. These authors could compose along with the objectives of this research a dialog with the teachers talks. The teachers could talk about who they are, what they think they are, and what they would like to be. Firstly, it is presented the trajectories of the ten teachers and some connections with professional, social and personal identities are done, highlighting their education, training and work experience. Further, the teachers professional identity is defined, as well as their performance in elementary schools, practice and relationships. It is important to highlight that Teachers professional identities are built throughout the time and involve different kinds of knowledge, different emotional aspects and other dimension that go beyond the school as family and society. It evidences the influence and role of collective and institutional dimensions as constituent elements of professional identities. Among the results found it is important to emphasize that the construction of teachers professional identities is permeated by various processes of teachers transformation, either through everyday experiences, decisions they make or not, their practices, or their professional and personal life continuities and discontinuities. Each person uses what he/she has learned, different knowledge in different ways, and this is originated from facts, decisions and situations faced that happened in different space of life. The professional identities are built from the social meaning of the profession, and thus, the professional identity is one of the identities of these authors (teachers), a part of the plurality of life. The dynamic feature of the construction of teachers identity group teachers, make them alike, but multiple in terms of diversity, where each musical educator compose themselves different from the others.